Analisis Perilaku Organisasi dalam Meningkatkan Pelayanan Kesehatan di Puskesmas - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Makmur, Afifah Idelma; Ayomi, Anasthasia F M; Rahmayati, Anisa (Universitas Pahlawan Tuanku Tambusai, 2025)
Community Health Center (Puskesmas) is a health institution engaged in providing health services to the surrounding community through the provision of several services in accordance with SOP standards and spread across several regions in Indonesia. Puskesmas can be called the front guard engaged in health institutions because they provide efficient, effective services, and can improve the welfare of the local community. Optimal service to the community is one of the obligations that must be carried out by the Puskesmas. However, the challenges faced by the Puskesmas can occur due to several factors. In addition, in providing quality services to the scope of the community can be influenced by several factors, one of which is organizational behavior. results of analysis related to organizational behavior in improving health services at Puskesmas. The writing method used in writing this journal is to use a qualitative type. The results obtained There are various main components of organizational behavior in exploring health services including communication patterns, decision-making processes, organizational culture and structure, leadership and management styles, group dynamics and team interactions, and individual behavior and attitudes. The conclusion is that organizational behavior in an agency is influenced by organizational culture. In the context of health centers, there are several organizational behaviors that can contribute to improving health services through organizational behavior, including effective communication, pro-patient organizational culture, effective leadership, performance evaluation and improvement, solid teamwork, and HR development.